Personality Traits Influencing Knowledge Sharing in Student-Supervisor Relationship: A Structural Equation Modelling Analysis - Memon, M.A. (World Scientific Publishing Co. Pte Ltd, 2016)
Although knowledge sharing (KS) and personality traits are primarily studied in business organisations, these issues are equally important for universities. However, few attempts have been made to investigate the relationship between personality traits and KS, particularly in the context of Malaysian higher education. The present study fills the research gap by examining the effects of personality traits - specifically agreeableness, conscientiousness and openness to experience - on KS in the student-supervisor relationship. Using probability sampling, data was collected from 175 doctoral students. Structural equation modelling was used to test the hypotheses. The findings suggest that agreeableness, conscientiousness and openness to experience are significantly and positively related to the KS behaviours of research supervisors. Openness to experience was revealed to be the most influential factor in the supervisor's level of KS. This is the first study to investigate the relationship between personality traits and KS in the context of the student-supervisor relationship, thus marking a significant contribution to the KS literature. The findings of this paper have implication for academics and higher education administrators. Â© 2016 World Scientific Publishing Co.